GEN Z, MISI DIASPORA, DAN AKSI SOSIAL: SEBUAH USULAN PENJANGKAUAN KEPADA DAN MELALUI GEN Z BERBASIS MISI DIASPORA DAN AKSI SOSIAL - Jonathan Wijaya (Jurnal Matetes STT Ebenhaezer, 2023)
Until today, Christian missions are a responsibility of the Christian community that should not be neglected. However, it is inevitable that the proclamation of the Gospel cannot always be accepted by everyone, especially Gen Z. Compared with social action, Christian missions are seen as bad by Gen Z. In fact, they are the largest community that has not been reached by the Gospel of Jesus Christ. Then a question arises from the author? How can they be won to Christ? Through literature analysis, the author will propose a diaspora mission and social action to reach Gen Z which is expected to encourage them to also reach out to others. This can be achieved by the author in 4 stages, namely first, the author provides an overview of Gen Z. After that, the author will provide an overview of the diaspora mission. Then, the author provides an analysis related to diaspora missions and Gen Z. Finally, the author will conclude that diaspora missions and social action are one of the proposals for reaching Gen Z and it is hoped that they can also reach other people to the Lord Jesus.